Damage tolerance assessment of AM 304L and cold spray fabricated 316L steels and its implications for attritable aircraft. (September 2021) - Jones, Rhys; Kovarik, Ondrej; Bagherifard, Sara; Cizek, Jan; Lang, Jeff
Highlights: Crack growth in CSAM and conventionally 316L follow the same equation. This equation coincides with that for SLM 316L in the as printed and HIPed condition. Their relationship between da/dN and the change in the potential energy/cycle is the same. Their relationship between Δ κ and the change in the potential energy/cycle is the same. Abstract: Assessing the damage tolerance and durability of additive manufactured (AM) materials is a key factor in the airworthiness certification of AM parts. Unfortunately, AM materials often exhibit a large degree of anisotropy, and their crack growth curves can differ markedly from those associated with the conventionally manufactured material. This paper reveals that when the changes in threshold and toughness due to the fabrication and annealing processes are accounted for, then crack growth in AM stainless steels can be represented by the same Hartman-Schijve equation that is associated with crack growth in the conventionally manufactured materials. Two different AM technologies and materials including 304L samples fabricated by wire arc additive manufacturing and 316L samples fabricated by cold spray deposition are considered for comparisons. The results are compared with the samples made of the corresponding material obtained through conventional manufacturing techniques. It is also shown that, for the cold spray specimens studied, there is a unique relationship between the crack growth rate (d a/ d N ) and the change in the potential energy per cycle, and that this relationship is independent of both the build direction and the post processing conditions. The experimental data also suggests that the reduced strain to failure associated with cold sprayed additively manufactured 316L parts left in the as sprayed condition may not significantly affect the durability/economic life of the cold spray fabricated 316L replacement parts. This suggests that cold spray additively manufactured parts parts may be attractive for use in attritable aircraft.